Effect of an antidisbiotic agent on the biosynthesis of fatty acids of liver lipids of rats which received palm oil on the background of dysbiosis - A. Levitsky; A. Markov; V. Velichko; I. Selivanskaya; A. Lapinskaya (Kazimierz Wielki University, 2022)
Background. To determine the effect of antidysbiotic agent on the biosynthesis of fatty acids of lipids in the liver of rats fed a high-fat diet (HFD) with palm oil against the background of dysbiosis. Methods. The HFD contained 15% palm oil. In a biological experiment, white rats were used, divided into 4 groups: the 1st group received a fat-free diet (FFD), the 2nd, 3rd, and 4th received HFD. In rats of the 3rd and 4th groups, dysbiosis was reproduced using lincomycin. Rats of the 4th group from the first day of the experiment received an antidysbiotic agent (inulin + quercetin, ADA) with food. The duration of feeding is 39 days. Liver lipids were divided into 3 fractions: neutral lipids (NL), phospholipids (PL), and free fatty acids (FFA). The fatty acid composition of the fractions was determined by gas chromatography. The "activities" of fatty acid synthase, palmitic acid elongase, and stearyl-CoA- desaturase (SCD18 and SCD16) were determined. Results. The presence of all classes of fatty acids (FA) in the liver lipids of rats treated with FFD was established.  Consumption of HFD with palm oil increased the content of NL in the liver by 6 times (gr. 2), and in group 3 by 8 times.  The introduction of ADA reduces the content of NL almost to the level of the 1st group.  The content of ω-3 polyunsaturated fatty acids (PUFA) decreases in the PL fraction in rats of the 3rd group and is restored in rats of the 4th group. In rats treated with HFD, the "activity" of synthase, SCD18 and very strongly SCD16 are reduced. Conclusion: The negative effect of palm oil on the background of dysbiosis on the biosynthesis of fatty acids in the liver, leading to hepatic steatosis and deficiency of ω-3 PUFA, can be prevented by the use of an antidysbiotic agent.